The Power of Mandatory Quality Disclosure: Evidence from the German Housing Market - Manuel Frondel; Andreas Gerster; Colin Vance (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
To mitigate information asymmetry problems with respect to the thermal quality of houses, many countries have introduced Energy Performance Certificates (EPCs). Using big data on real estate advertisements that cover large parts of the German housing market, this paper empirically investigates the consequences of a shift from a voluntary to a mandatory quality disclosure regime on the offer prices of houses. Motivated by a stylized theoretical model, we test the following key hypothesis: Prices for houses whose owners would not voluntarily disclose their house's energy consumption in real estate advertisements should decrease upon a shift to a mandatory disclosure scheme. Employing an instrumental variable approach to cope with the endogeneity of disclosure decisions, our analysis demonstrates the relative advantage of mandatory over voluntary disclosure rules.
Keywords: D82; L15; Q58; 330